Escherichia coli: Germ Theory, A Bacterial Killer Mechanism, Virulence, Pathogenicity Islands (PAIs), Pathogenesis, Secretion Systems - Nurdan Filik; Fethi Filik (Acta Natura et Scientia)
Why do bacteria damage their hosts? After bacteria bypass the immune system, bacterial virulence enables a host to replicate and propagate within a host in part by demolishing or escaping host defenses. Bacterial pathogens possess an array of specific killer mechanisms that submit virulence and the capacity to intercept host defence mechanisms. Mechanisms of virulence are often mediated by the subversion of normal aspects of host biology. Also, recently, three novels but wide themes have emerged in the field of bacterial virulence: a bacterial killing mechanism, secretion systems and pathogenicity islands. So, pathogen changes the host function so as to support the pathogen’s survival or multiplication. Such subversion is often mediated by the specific interaction of bacterial effector molecules with host-encoded proteins and other molecules. Escherichia coli is a considerable and diverse micro alive. E. coli needs only to acquire a mix of mobile genetic elements to become a pathogen capable of causing diseases. The worldwide burden of these diseases is staggering, with hundreds of millions alive affected annually. E. coli strains have been well a bacteria model, and each uses an arsenal of virulence and toxin to subvert host cellular functions to reenforce its virulence. This review focuses on the drastic and different pathogenic mechanisms that are used by various E. coli strains.